Effect of cooking processes on tilapia aroma and potential umami perception - Danni Zhang; Charfedinne Ayed; Ian D. Fisk; Yuan Liu (Food Science and Human Wellness)
Tilapia is a freshwater fish group with a sustainable prospect but suffers off-notes appearing during cooking processes. To promote pleasant odorants by thermal cooking processes, tilapia fillets were cooked in different ways (roasting, microwave-heating, boiling and steaming). Their aroma profiles were analysed with special focus on off-notes and umami-enhancing odorants by principal component analysis, and correlated with the heating time, colour, moisture and water activity by partial least squares regression analysis. Results showed that the “green” and “earthy” off-notes were highly correlated with the boiling process (excess of water, short heating time), while most of the umami-enhancing odorants had a high association with the roasting process (low water content, long heating time, better Maillard reaction). This study indicated that roasting is the most adapted cooking process promoting Maillard-derived aromas, umami-enhancing aromas and meanwhile, reducing off-notes. This research helps in understanding the off-note generation in tilapia and promoting desirable umami-enhancing odorants.